Concentrated insulins in current clinical practice. (February 2019) - Schloot, Nanette C.; Hood, Robert C.; Corrigan, Sheila M.; Panek, Robert L.; Heise, Tim
Abstract: New concentrated insulins (exceeding 100 units/mL) and dedicated devices have recently become available, offering new treatment options for people with diabetes, for basal and prandial insulin supplementation. The concentrated insulin formulations range from 2-fold concentration (insulin lispro 200 units/mL) with rapid-acting prandial action to 5-fold concentration (human regular insulin, 500 units/mL) with basal and short-acting prandial actions. Long-acting basal insulins include degludec 200 units/mL and glargine 300 units/mL. Concentrated insulins have been developed with the goal of easing insulin therapy by reducing the volume and number of injections and in some cases making use of altered pharmacokinetic and pharmacodynamic properties. This review summarizes the unique characteristics of each concentrated insulin to help healthcare providers and people with diabetes understand how to best use them.